Member-focused PPS : sustainability of a business model in a changing industry - Ojah, Kalu; Urban, Angela, active 2018 (London : Wits Business School, 2018)
In July 2017, Izak Smit, newly appointed CEO of the Professional Provident Society (PPS), one of very few remaining financial services firms in South Africa to operate as a mutual society and the only one that focused exclusively on the professional segment, reflected on his first year as CEO. The year had seen changes to the distribution model, the introduction of a financial planning division and, in January, the launch of business short-term insurance - the latest in the company's short-term insurance offering. Despite the fact that in July 2017, the Financial Intermediaries Association (FIA) had named PPS the winner of the insurer of the year in the long-term risk category, PPS could not be complacent. Was its niche in the insurance industry sufficiently deep? Could the dynamics of the financial markets have a negative impact on the company's business model?
Originally Published In Ojah, K., & Urban, A. (2018). Member-Focused PPS: Sustainability of a Business Model in a Changing Industry. WBS-2018-17. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Smit, Izak; Professional Provident Society of South Africa; Fraternal organizations -- South Africa -- Management -- Case studies; Insurance -- South Africa -- Management -- Case studies